2019
DOI: 10.1093/mnras/stz3485
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization of the non-thermal X-ray emission of gamma-ray pulsars

Abstract: We report on a detailed spectral characterization of the non-thermal X-ray emission for a large sample of gamma-ray pulsars in the second Fermi LAT catalogue. We outline the criteria adopted for the selection of our sample, its completeness, and critically describe different approaches to estimate the spectral shape and flux of pulsars. We perform a systematic modelling of the pulsars' X-ray spectra using archival observations with XMM-Newton, Chandra and NuSTAR and extract the corresponding non-thermal X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
(101 reference statements)
0
12
1
Order By: Relevance
“…J0218 is part of a small but diverse population of MSPs with a well-characterized broad-band non-thermal energy distribution. Several of these MSPs have an 'inverted' spectrum in X-rays (where 𝐸 2 𝑑𝐹/𝑑𝐸 decreases with energy), quite different from that of J0218 as we have reported here, see Figure 3 of Coti Zelati et al (2020). We also note that the fitted magnetic gradient 𝑏 for J0218 and other MSPs within the synchro-curvature model (Torres 2018) is larger than for normal pulsars.…”
Section: Discussioncontrasting
confidence: 42%
“…J0218 is part of a small but diverse population of MSPs with a well-characterized broad-band non-thermal energy distribution. Several of these MSPs have an 'inverted' spectrum in X-rays (where 𝐸 2 𝑑𝐹/𝑑𝐸 decreases with energy), quite different from that of J0218 as we have reported here, see Figure 3 of Coti Zelati et al (2020). We also note that the fitted magnetic gradient 𝑏 for J0218 and other MSPs within the synchro-curvature model (Torres 2018) is larger than for normal pulsars.…”
Section: Discussioncontrasting
confidence: 42%
“…In order to investigate this question, the characteristics of the 18 soft γ-ray pulsars were compared with those of the 77 non-recycled LAT-detected pulsars in the Second Fermi Pulsar Catalog . Surprisingly, it was found that the soft γ-ray pulsars are all fast rotators and on average ∼ 9.3 times younger and ∼ 43 times more energetic than the Fermi LAT sample (see also Coti Zelati et al 2020 for a recent assessment). The majority (11 sources) exhibits broad, structured single pulse profiles, and only six have double (or even multiple, Vela) pulses (see Fig.…”
Section: Psr J1846-0258 Showing Magnetar-like Behaviourmentioning
confidence: 99%
“…Characterizing the non-thermal multi-wavelength spectrum of a large sample of MSPs (as done, for example, in [46,47] mostly for pulsars) would set population studies of MSP emission mechanisms on more solid grounds and improve our understanding of the γ-X connection. Dedicated analyses of archived X-ray observations and existing source catalogs is another path to refine the spectral selection of MSP candidates, distinguishing them from extragalactic objects and other Galactic sources as cataclysmic variables and intermediate polars.…”
Section: Introduction a Mysterious Excess Discovered Atmentioning
confidence: 99%